Planeación Financiera en la empresa “Franquiciado Disensa” del señor Lauro Joselito Jiménez Abad, de la ciudad de Amaluza, periodos 2023-2027 - Loarte Lalangui, Mariuxi Elizabeth (2023)
The present research Curricular Integration Work called: "FINANCIAL PLANNING IN THE COMPANY “FRANQUICIADO DISENSA” DEL SEÑOR LAURO JOSELITO JIMÉNEZ ABAD, AMALUZA CANTON , PERIODS 2023-2027; It was executed in order to effectively and efficiently contribute to the owner being able to optimize the available resources, and also to achieve a great profitability in the coming years and to consider some alternatives that will contribute to decision making for better financial benefits. In order to comply with the proposed objectives, a series of mathematical calculations were carried out to allowed the assessment of the financial and economic structure through the financial diagnosis where vertical analysis, financial indicators and SWOT matrix were applied. It continue with the process with the development of the Financial Planning, where the forecasts of sales and purchases were prepared for the periods 2023-2027 also the process that was carried out using the seasonality index method, later the program of cash inflows and outflows is presented, the same one that allowed the cash budget to be made in which it tells us how much is the excess effective balance. In addition, the Proforma Financial Statements were developed, showing the future income and expenses for the following years, as well as the expected financial position at the end of the forecast period, for this process the sales increase percentage method was used; except for personnel expenses, the same that was determined with the salary percentage, it culminates with the representation of the break-even point of the different projected years. The results obtained from the Proforma States for the year 2027 the company will have assets of $596,288.99, liabilities of $253,599.61, equity of $342,689.39, income of $1,084,614.56; costs of $909,396.47; expenses of $144,900.89 and net income of $30,317.19. It is concluded that Financial Planning will allow the owner to know the future inflows and outflows of money and thus be able to prevent unexpected situations.